Hoveniae Semen Seu Fructus Ethanol Extract Exhibits Anti-Inflammatory Activity via MAPK, AP-1, and STAT Signaling Pathways in LPS-Stimulated RAW 264.7 and Mouse Peritoneal Macrophages - Jeong, Yun Hee; Oh, You-Chang; Cho, Won-Kyung; Yim, Nam-Hui; Ma, Jin Yeul (Mediators of Inflammation, 2019)
Hoveniae semen seu fructus (HSF, fruit and seed of Hovenia dulcis Thunb) is an important traditional herbal medicine and food supplement in East Asia for the treatment of liver diseases, alcohol poisoning, obesity, allergy, and cancer. HSF has also been reported to have anti-inflammatory activity, but the cellular mechanism of action is not fully understood. We assessed the anti-inflammatory properties of an HSF ethanol (HSFE) extract and explored its precise mechanism. The ability of HSFE to suppress inflammatory responses was investigated in a murine macrophage cell line, RAW 264.7, and mouse primary macrophages. Secretions of NO, proinflammatory cytokines, inflammatory factors, and related proteins were measured using the Griess assay, ELISA, Western blot analysis, and real-time PCR, respectively. In addition, the main components of HSFE were analyzed by HPLC, and their anti-inflammatory activity was confirmed. Our results showed that pretreatment of HSFE markedly reduced the expression of NO and iNOS without causing cytotoxicity and significantly attenuated secretion of proinflammatory cytokines, including TNF-α, IL-6, and IL-1β. In addition, HSFE strongly suppressed phosphorylation of MAPK and decreased the activation of AP-1, JAK2/STAT, and NF-κB in LPS-stimulated RAW 264.7 cells in a concentration-dependent manner. Furthermore, HSFE strongly suppressed the inflammatory cytokine levels in mouse peritoneal macrophages. Also, as a result of HPLC analysis, three main components, ampelopsin, taxifolin, and myricetin, were identified in the HSFE extract, and each compound effectively inhibited the secretion of inflammatory mediators induced by LPS. These findings show that HSFE exerts anti-inflammatory effects by suppressing the activation of MAPK, AP-1, JAK2/STAT, and NF-κB signaling pathways in LPS-stimulated macrophages. In addition, the anti-inflammatory efficacy of HSFE appears to be closely related to the action of the three main components. Therefore, HSFE appears to be a promising candidate for the treatment of inflammatory diseases.